2016
DOI: 10.1111/cbdd.12708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Natural and Synthetic 1,4‐naphthoquinones as Inhibitors of Monoamine Oxidase

Abstract: Previous reports have documented that 1,4-naphthoquinones act as inhibitors of the monoamine oxidase (MAO) enzymes. In particular, fractionation of the extracts of cured tobacco leafs has led to the characterization of 2,3,6-trimethyl-1,4-naphthoquinone, a non-selective MAO inhibitor. To derive structure-activity relationships for MAO inhibition by the 1,4-naphthoquinone class of compounds, this study investigates the human MAO inhibitory activities of fourteen structurally diverse 1,4-naphthoquinones of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…87) It was later found that echinochrome (20) is a non-competitive acetylcholinesterase inhibitor, which opens up prospects for the use of echinochrome for the treatment of neuromuscular disorders, as well as Alzheimer's and Parkinson's diseases. 88) The monoamine oxidase (MAO) enzymes are of considerable pharmacological interest and inhibitors are used in the clinic for the treatment of major depressive disorder and neurodegenerative diseases. 2,3,6-trimethyl-1,4-naphthoquinone (70) (Fig.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…87) It was later found that echinochrome (20) is a non-competitive acetylcholinesterase inhibitor, which opens up prospects for the use of echinochrome for the treatment of neuromuscular disorders, as well as Alzheimer's and Parkinson's diseases. 88) The monoamine oxidase (MAO) enzymes are of considerable pharmacological interest and inhibitors are used in the clinic for the treatment of major depressive disorder and neurodegenerative diseases. 2,3,6-trimethyl-1,4-naphthoquinone (70) (Fig.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…Literatures have documented the MAO inhibitory activity of 1,4‐naphthoquinones. In this view, Mostert et al investigated the recombinant hMAO‐B inhibitory activities of several structurally diverse 1,4‐naphthoquinones of natural and synthetic origin ( 134‐138 ; Figure ). The hMAO‐B inhibition potencies ranged from 0.860 to 24.8 µM.…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
“…1,4‐Naphthoquinone derivatives ( 134‐138 ) . hMAO, human monoamine oxidase; IC 50 , half maximal inhibitory concentration…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
See 2 more Smart Citations